2001
DOI: 10.1111/j.1469-8749.2001.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuromotor development from 5 to 18 years. Part 1: timed performance

Abstract: Timed performance in specific motor tasks is an essential component of a neurological examination applied to children with motor dysfunctions. This article provides centile curves describing normal developmental course and interindividual variation of timed performances of non‐disabled children from 5 to 18 years. In a cross‐sectional study (n=662) the following motor tasks were investigated: repetitive finger movements, hand and foot movements, alternating hand and foot movements, sequential finger movements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 18 publications
0
47
0
Order By: Relevance
“…Five studies reported large inter-subject variability within age groupings32 43 48 49 54 and 10 studies reported significant differences between adolescent males and females for certain sensorimotor mechanisms 1217 28 32 33 42 44 49 51 52. Two studies reported no differences between sexes for the observed measures 13 50.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies reported large inter-subject variability within age groupings32 43 48 49 54 and 10 studies reported significant differences between adolescent males and females for certain sensorimotor mechanisms 1217 28 32 33 42 44 49 51 52. Two studies reported no differences between sexes for the observed measures 13 50.…”
Section: Resultsmentioning
confidence: 99%
“…No studies were comprehensively longitudinal (ie, longitudinal over the entire age range) or systematically representative of the spectrum of adolescent ages. However, some studies did utilise samples that went beyond simple, cross-sectional designs 17 32 33 38 4244 4850 52 53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the range of differences between individuals within a given group (e.g. gender, age) is often quite large when compared with the mean differences between groups (21,23,24).…”
mentioning
confidence: 99%
“…In a study by Largo et al, the average for SLS amongst typically developing five year olds was approximately seven to eight seconds compared to approximately four seconds in the current study. It is important to note that the children in the current study were slightly younger in terms of their corrected age and that the SLS testing procedure in the Largo et al study differed a little (Largo et al, 2001). …”
Section: Discussionmentioning
confidence: 99%